أثر استخدام استراتيجيتي أورايلي وبوليا في تحصيل مادة العلوم لدى طالبات الصف الثاني المتوسط - البهادلي، أمل مهدي جبر; حمزة، منتهى قاسم عبد (جامعة الكوفة - كلية التربية للبنات, 2019)
هدف البحث الحالي التعرف على فاعلية استراتيجيتي بوليا واورايلي في تحصيل مادة العلوم لدى طالبات الصف الثاني متوسط، ولتحقيق هدف البحث تم صياغة الفرضية الصفرية: 1- لا توجد فروق ذو دلالة إحصائية عند مستوى دلالة (0.05) بين متوسط درجات طالبات المجموعات الثلاث )المجموعة التجريبية الأولى التي ستدرس المادة المقررة وفق استراتيجية )بوليا( والمجموعة التجريبية الثانية التي ستدرس المادة نفسها وفق استراتيجية (اورايلي( والمجموعة الضابطة التي ستدرس نفس المادة وفق الطريقة الاعتيادية في اختبار التحصيل. وقد اقتصر البحث الحالي على طالبات الصف الثاني متوسط في المدارس المتوسطة في مركز مدينة الديوانية. استعملت الباحثتان التصميم التجريبي لمجتمع بحثها مكون من طالبات الصف الثاني متوسط إذ تم اختبار متوسطة الإيمان بصورة عشوائية لتمثيل عينة البحث، كما تم اختبار شعبة )أ( عشوائياً لتمثل المجموعة التجريبية الأولى وشعبة (ب) المجموعة التجريبية الثانية وشعبة (ج) المجموعة الضابطة، وقد بلغ عدد طلاب عينة البحث (78) طالبة وبواقع (26) طالبة للمجموعة التجريبية الأولى و(27) طالبة للمجموعة التجريبية الثانية و(25) طالبة للمجموعة الضابطة. تم التحقق من تكافؤ المجموعتين من خلال العمر الزمني ودرجات التحصيل السابق واختبار الذكاء والمعلومات السابقة. بنت الباحثتان أدوات البحث التي تمثلت باختبار تحصيلي مكون من (30) فقرة من نوع الاختيار من متعدد. تم تطبيق التجربة في الفصل الدراسي الثاني إذ كانت بداية التدريس الفعلي (24/2/2019) ونهاية التدريس الفعلي (24/4/2019). وللحصول على النتائج تم معالجة البيانات إحصائيا باستخدام تحليل التباين الأحادي One-Way (ANOVA) واختبار شيفيه (Scheffe Test) وأظهرت النتائج ما يأتي: 1- تفوق المجموعتين التجريبية الأولى والثانية على المجموعة الضابطة في متغير التحصيل من خلال نتائج البحث قدمت الباحثتان عددا من التوصيات أهمها: 1- تعريف المدرسات باستعمال استراتيجيتي (اورايلي) و (بوليا) في تدريس مادة العلوم. 2- توجيه مدرسي العلوم للاهتمام باستعمال استراتيجية (بوليا) و(واورايلي) في تدريس مادة العلوم. 3- توجيه أنظار وأنشطة تعمل على تنمية مهارة تقويم الحجج لدى الطلبة. ولقد قدمت الباحثتان عددا من المقترحات أهمها: 1- دراسة إثر استراتيجيتي (بوليا) و(واورايلي) في متغير الذكاءات المتعددة. 2- دراسة إثر استراتيجيتي (بوليا) و(اورايلي) في متغير التفكير المنطقي.
This research aimed to determine the effectiveness of the Polya and Orielly strategies in the achievement, in the science of second grade students is average. To achieve the research aims, null hypotheses were formulated as the following: 1- There are no statistically significant differences at the level of significance (0.05) among the means scores of the students of the three groups (the first experimental group studied the material according to the Polya strategy and the second experimental group which studied the same material according to the Orielly strategy and the control group that studied the same material accordance to the normal method in achievement test. The current research was confined on the second grade is average students in average schools in Diwaniyah city center. The researcher used the experimental design of a research society composed of second is average A school of average Al-Eman was randomly selected to represent the research sample, class (A) was chosen to represent the first experimental group, the second experimental group (B) and (C) the control group, the number of students in the research sample was 78 students, 26 students for the first experimental group, 27 students for the second experimental group and 25 students for the control group. The equivalence was verified by age, past achievement scores, intelligence test, prior information, and evaluating arguments test. The researcher built the research tools, which consisted of an achievement test consisting of (30) items multiple choice types, and a test of evaluating arguments consisting of (57) items. The experiment was applied in the second semester as the beginning of actual teaching (24/2/2019) and the end of actual teaching (24/2/2019). Results were statistically analyzed using one-way ANOVA and Scheffe Test. Results showed the following: 1- The first and second experimental groups predominate on the control group in the achievement variable. 1- The school of science and interesting using the Polya and Orielly strategies in teaching science. 2- Guidance and activities to develop the skill of evaluating the arguments at the request. The researcher also made a number of proposals, including: 1- Study the effect of the Polya and Orielly strategies in the multiple intelligences variable. 2- studying the impact of the Polya and Orielly strategies in the logical thinking.
Keywords: الإستراتيجية -- استراتيجية أورايلي -- استراتيجية بوليا -- تدريس العلوم -- التحصيل الدراسى -- الصف الثاني المتوسط